The Nature of Language and The Nature of Education in The Language Education Policy - Ferlya Elyza; Fauzia Fauzia (Jurnal Dedikasi Pendidikan, 2020)
This article proposes about the nature of language and the nature of education in frame of language education policy in Indonesia. Its discussion is intended to be one of considerations in how to design and formulate some policies in education, especially language education policy in the era of the industrial revolution 4.0. The primary discussion is started by presenting some critical expert views on the nature of language along with its relationship to the nature of education in general. The understanding on both of these terms will lead to the appropriate decision on the future language education policy. Comprehensive understanding on each of the terms enables readers, stakeholders, teacher practitioners, and government to be open-minded to decide the future steps in designing and formulating the education policy especially to language education policy. The developed analysis will be based on the educational phenomenon which happenned in all regions both local and national areas.